Mongolia health situation: based on the Global Burden of Disease Study 2019 - Odgerel Chimed-Ochir; Vanya Delgermaa; Ken Takahashi; Oyuntsetseg Purev; Amarzaya Sarankhuu; Yoshihisa Fujino; Narantuya Bayarmagnai; Otgontuya Dugee; Ryenchindorj Erkhembayar; Battur Lkhagvaa; Chimedsuren Ochir; Tumenjavkhlan Sosorburam; et al. (BMC, 2022)
Abstract Background Over the past few decades, economic, political, and social changes have directly and indirectly affected the health of the Mongolian population. To date, no comprehensive analysis has been conducted on the burden of diseases in this country. Thus, we aimed to describe the leading causes of death and disabling conditions and their trends between 1990 and 2019 in the Mongolian population. Methods We used the data from the Global Burden of Disease (GBD) 2019 study. In the current study, we examined life expectancy at birth, healthy life expectancy, the 20 leading causes of death, years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted-life-years (DALYs), and the contribution of major risk factors to DALYs in Mongolia. Findings The life expectancy at birth in Mongolia has gradually increased since 1995 and reached 63.8 years for men and 72.7 for women in 2019. The highest increase in the age-standardised death rate between 1990 and 2019 occurred in alcohol use disorders (628.6%; 95% UI 10.0-1109.6) among men, and in liver cancer (129.1%; UI 65.3-222.4) among women. Ischaemic heart disease and stroke showed the highest rates of death, YLLs, and DALYs among both men and women. In 2019, the highest age-standardised rates of DALYs were attributable to high systolic blood pressure and dietary risks. Interpretation Although Mongolia saw substantial improvements across many communicable diseases, maternal and neonatal disorders, and under-5 mortality between 1990 and 2019, non-communicable diseases remained leading causes of mortality. The mortality from the most preventable causes such as injury, alcohol use, and dietary risks remain substantially high, suggesting that individual and social efforts are needed to tackle these diseases. Our analyses will support the development of policy priorities and action plans in multiple sectors to improve the overall health of the Mongolian population. Funding Bill & Melinda Gates Foundation.